Cytogenetic evaluation of mesenchymal stem/stromal cells from patients with myelodysplastic syndromes at different time-points during ex vivo expansion. (April 2016) - Kouvidi, Elisavet; Stratigi, Aikaterini; Batsali, Aristea; Mavroudi, Irene; Mastrodemou, Semeli; Ximeri, Maria; Papadaki, Helen A.; Pontikoglou, Charalampos G.
Highlights: BM MSCs from MDS patients exhibit genetic instability during ex vivo expansion. Chromosomal abnormalities in MDS-derived MSCs do not affect growth characteristics. BM MSCs and HCs from MDS patients do not derive from the same clone. Abstract: Mounting evidence suggests that in myelodysplastic syndromes (MDSs) bone marrow (BM) mesenchymal stem/stromal cells (MSCs) possess abnormal characteristics and are actively involved in disease pathogenesis. Nevertheless, it is controversial whether these cells harbor clonal cytogenetic aberrations. To probe more deeply into this issue, in the present study we used conventional G-banding and FISH analysis to assess the clonal chromosomal abnormalities of hematopoietic cells (HCs) and cultured MSCs, from 29 MDS patients and 25 healthy individuals, at early, intermediate and late passage. Variable clonal cytogenetic aberrations were detected in HCs from 31% and in MSCs from 34% of MDS patients. Clonal chromosomal abnormalities in MSCs were detected even in patients without aberrations in HCs. They were mostly numerical and always differed from those in HCs from the same individual. Clonal chromosomal abnormalities did not seem to confer a proliferative and/or survival advantage to MSCs. HCs from normal donors harbored no cytogenetic abnormalities, whereas trisomy of chromosome 5 was detected in MSCs from 16% of healthy individuals, in line with other studies. Our results suggest that MDS-derived BM-MSCs are genetically unstable. The significance of this observation in the biology of MSCs and MDS pathogenesis is still unknown and warrants further evaluation.